Case series of patients with laboratory-confirmed Marburg virus disease in 2023 in Equatorial Guinea - Ondo Ndoho, Florentino Abaga; Fontana, Luca; Avomo, Candido Ondo Ondo; Mikue, Ladislao Ekiri Ngomo; Eyemam, Domitila Ñadang Fuga; Nguere, Micaela Ayang; Mometolo, Ilda Elobe; Nzang, Rosalia Nazang Bibang; Maye, Damaso Mitogo Nguema; Hernandez Suarez, Yosbanis; Esono, Salvador Eduardo; Miko Ayang, José Antonio; et al. (Clinical infectious diseases, 2025)
Marburg virus disease (MVD) is a severe viral infection caused by the Marburg marburgvirus species. In February 2023, Equatorial Guinea declared its first outbreak. This case series describes the natural history of MVD in 5 patients with laboratory-confirmed disease.Patients with confirmed MVD who were admitted to the national treatment center in Bata, Equatorial Guinea were monitored for vital signs and symptoms. Comprehensive clinical data were collected to understand the progression and outcome of the disease.Five patients were confirmed to have MVD. Three male healthcare workers received a diagnosis diagnosed early in their disease and subsequently survived. The other 2 patients, both female, were admitted later in their disease progression and died within 24 hours of admission. Four patients received remdesivir under a protocol for the monitored emergency use of unregistered and experimental interventions. The early symptoms were nonspecific, with rapid progression to more severe conditions in the later stages of the disease. Early treatment with remdesivir showed the drug to be well tolerated.Contrary to some reports and the recommended case definition for MVD, our patients presented with a rash but did not exhibit vomiting or diarrhea. Hemorrhagic signs were solely observed in the terminal stage, preceding demise. Despite the limited sample size, these findings emphasize the importance of tailoring the case definition to the specific outbreak. Further evidence on the efficacy and safety of therapeutics for MVD, including remdesivir, should be gathered through well-designed trials during future epidemic responses.
Gesehen am 03.11.2025. Online ahead of print